2015
DOI: 10.1007/s10802-015-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Peer Regulation of Adolescent Emotion: Associations with Depressive Symptoms

Abstract: Emotion socialization by close relationship partners plays a role in adolescent depression. In the current study, a microsocial approach was used to examine how adolescents' emotions are socialized by their mothers and close friends in real time, and how these interpersonal emotion dynamics are related to adolescent depressive symptoms. Participants were 83 adolescents aged 16 to 17 years who participated in conflict discussions with their mothers and self-nominated close friends. Adolescents' positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 64 publications
5
48
0
Order By: Relevance
“…Very few studies have examined friends' responses in relation to adolescent internalizing symptoms, but there are some consistencies with the parent literature. In crosssectional study of typically-developing adolescents, Lougheed et al (2015) reported that friends of adolescents with higher depressive symptoms were less likely to respond supportively to adolescents' positive emotions compared with friends of adolescents with lower depressive symptoms. There are several possible interpretations for this finding, such as considering the friend's own level of depressive symptoms.…”
Section: Internalizing Symptomsmentioning
confidence: 98%
See 1 more Smart Citation
“…Very few studies have examined friends' responses in relation to adolescent internalizing symptoms, but there are some consistencies with the parent literature. In crosssectional study of typically-developing adolescents, Lougheed et al (2015) reported that friends of adolescents with higher depressive symptoms were less likely to respond supportively to adolescents' positive emotions compared with friends of adolescents with lower depressive symptoms. There are several possible interpretations for this finding, such as considering the friend's own level of depressive symptoms.…”
Section: Internalizing Symptomsmentioning
confidence: 98%
“…However, Shortt et al (2016) noted the importance of considering parent and adolescent gender, as depressed boys and girls have been found to receive different responses from their mothers and fathers. In a cross-sectional study of typically-developing adolescents, Lougheed et al (2015) reported that parents were less likely to respond supportively to positive and negative emotions for adolescents with higher depressive symptoms. Thus, the pattern of findings is divergent when examining clinical and community samples, as well as mothers and fathers.…”
Section: Internalizing Symptomsmentioning
confidence: 99%
“…Adolescent hyper-emotionality is well-documented particularly in association with behaviors that involve social interaction such as with peers and parents (Steinberg and Morris, 2001). Other behaviors in which hyper-emotionality is clearly displayed during adolescence include risk taking and reward seeking, although these behaviors are strongly moderated by the social context in which they occur (Lougheed et al, 2015; Somerville et al, 2010; Steinberg, 2008). …”
Section: Heightened Emotionality In Adolescence: Form and Functionmentioning
confidence: 99%
“…Adolescents vary on a wide variety of dimensions that include temperament 40 , sensitivity to parenting 41 , biological vulnerabilities 42, 43 , psychopathology 44, 45 , personality 46 and relationship history 4748 . These individual differences between adolescents may moderate the association between parenting practices and adolescent outcomes and further refine the meaning of sensitive attunement to encompass the ways in which parents adapt their practices to the characteristics of a particular adolescent.…”
Section: Challenges To Implementing Parenting Practicesmentioning
confidence: 99%